ADVANTAGES OF INTEGRATING ACTIVITIES IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Lazzat Ilesova (Modern American Journals, 2025)
This article explores the advantages of integrating activities in preschool educational institutions, emphasizing its role in fostering holistic development of young children. The study highlights how integration helps in combining cognitive, social, emotional, and physical learning into a unified process, ensuring that children perceive knowledge not as separate subjects but as interconnected experiences. Such an approach allows children to build strong foundations in communication, creativity, problem-solving, and collaboration. The research also outlines how integrated learning enhances motivation, supports differentiated instruction, and prepares children for future educational stages by aligning learning with natural developmental needs. The paper is based on pedagogical theories, practical experiences, and comparative analysis of existing preschool methodologies. Findings indicate that integration is not only an effective method to strengthen children’s readiness for school but also a means of nurturing critical skills such as adaptability, independence, and cooperation in group settings.
Keywords: preschool education, integrated learning, holistic development, child-centered approach, pedagogy, early childhood development.